Hypoglycemia Among Type 1 Diabetes Patients After Insulin Use in Southwest Ethiopia - Yosef, Tewodros (Frontiers in Endocrinology, 2021)
Introduction Glycemic control is a valuable goal for people with diabetes; however, the greatest challenge to achieving tight glycemic control is hypoglycemia. Hypoglycemic events are probably common in type 1 diabetes; however, little is known about hypoglycemia in Ethiopia. Therefore, this study aimed to assess the prevalence and the associated factors of hypoglycemia among type 1 diabetes (T1D) patients after insulin use at Metu Karl Referral Hospital in southwest Ethiopia. Materials and Methods A hospital-based cross-sectional study was conducted among 242 T1D patients at Metu Karl Referral Hospital in southwest Ethiopia. The prevalence of hypoglycemia was assessed by a structured questionnaire through a face-to-face interview in which all the possible symptoms of hypoglycemia were included. If the patients reported that they had experienced the symptoms at least two times in a month and the symptoms were relieved upon consuming sugar/candy/honey, such cases were considered to have had a hypoglycemic episode. Binary logistic regression analysis was done to identify the factors associated with the occurrence of hypoglycemia. Results Out of 242 T1D patients interviewed, 114 (47.1%) had self-reported hypoglycemia. The most reported symptom of hypoglycemia was sweating (91.7%), followed by dizziness and hunger and nausea with a prevalence of 24.8 and 14.5%, respectively. The study also found that educational level with reading and writing skills up to primary level [adjusted odds ratio, AOR = 0.41; 95% confidence interval, CI (0.19–0.88)] and secondary level and above [AOR = 0.32, 95% CI (0.14–0.70)], poor knowledge of diabetes [AOR = 2.26, 95% CI (1.06–4.84)], good knowledge of insulin self-administration [AOR = 0.54, 95% CI (0.30–0.99)], and duration of insulin use ≥5 years [AOR = 3.93, 95% CI (1.44–10.7)] were factors associated with hypoglycemia. Conclusions The prevalence of hypoglycemia was found remarkable. We can conclude that hypoglycemia is of public health importance among T1D patients. Since the study assesses hypoglycemia after insulin injection, this prevalence may be due to the poor practice of insulin injection. Therefore, imparting education on the proper technique of insulin administration should be considered at each follow-up visit.